Complications associated with laparoscopic sleeve gastrectomy – a review - Paulina Woźniewska; Inna Diemieszczyk; Hady Hady (Gastroenterology Review)
Laparoscopic sleeve gastrectomy (LSG) is an essential bariatric procedure performed in obese patients, which provides significant weight loss and has a positive impact on obesity-related diseases. However, as with any surgical procedure, it carries the risk of complications. The complications that can arise in patients following LSG are divided into acute (diagnosed within 30 days after the surgery) and late. Early complications that require rapid management include haemorrhage (intraluminal or extraluminal), leak in the staple line, and abscess formation. Late complications include gastric stenosis, nutrient deficiencies, mediastinal pouch migration, and the development or exacerbation of gastroesophageal reflux diseases. In this review, we present the basic information about most common complications following LSG, and their symptoms, diagnostic tools, and management.